Efforts to Improve Early Literacy Recognition Skills Using Letter Card Media for Students at RA Darul Ulum - Mustafidah, Hidayatul; Ibroiyah (Journal of Indonesian Primary School, 2025)
This study aims to evaluate the effectiveness of using multimedia flashcards in improving letter recognition skills in students at RA Darul Ulum. This study compared two groups of students: an experimental group using multimedia flashcards and a control group using traditional teaching methods. The results showed that the use of multimedia flashcards significantly improved students' ability to recognize letters and associate them with letter sounds. The experimental group showed a more significant improvement compared to the control group in terms of letter recognition and phonemic understanding. In addition, multimedia flashcards also increased student engagement and motivation. Students in the experimental group were more active in participating in learning and were more interested in the material being taught. The results of the motivation survey showed that students who used multimedia flashcards enjoyed learning more, because of the interesting interactive features, such as pictures and sounds that accompany the letters. However, this study also found several challenges, such as limited access to technology for some students and the relatively short duration of the intervention. Nevertheless, the results showed that multimedia flashcards were very effective in improving letter recognition skills and could be used as a useful method in elementary education learning. This study suggests that RA Darul Ulum continue to integrate the use of multimedia flashcards into the early childhood education curriculum to support the development of students' literacy skills.